Effect of Clay Addition on Mechanical Properties of Unsaturated Polyester/Glass Fiber Composites - Kusmono; Zainal Arifin Mohd Ishak (International Journal of Polymer Science)
Unsaturated polyester (UP)/glass fiber/clay composites were prepared by hand layup method. The effect of clay loading on the morphological and mechanical properties of UP/glass fiber composites was investigated in this study. X-ray diffraction (XRD) was used to characterize the structure of the composites. The mechanical properties of the composites were determined by tensile, flexural, unnotched Charpy impact and fracture toughness tests. XRD results indicated that the exfoliated structure was found in the composite containing 2 wt% of clay while the intercalated structure was obtained in the composite with 6 wt% of clay. The tensile strength, flexural strength, and flexural modulus of the composites were increased in the presence of clay. The optimum loading of clay in the UP/glass fiber composites was attained at 2 wt%, where the improvement in in tensile strength, flexural strength, and flexural modulus was approximately 13, 21, and 11%, respectively. On the other hand, the highest values in impact toughness and fracture toughness were observed in the composites with 4 wt% of clay.